Radical Medicine: The International Origins of Socialized Health Care in Canada - Razumenko, Fedir (Labour / Le Travail, 2020)
The article reviews the book, "Radical Medicine: The International Origins of Socialized Health Care in Canada," by Esyllt W. Jones.